Pengaruh Gaya Kepemimpinan Dan Reward Punishment Terhadap Kinerja Karyawan Pada Pt. Bumi Barito Utama Kantor Cabang Banjarmasin - Siti Nur Chaliza (BIMA: Jurnal Bisnis dan Manajemen, 2022)
The aims of this study are: (1) To know and analyze whether leadership style and reward punishment have a simultaneous significant effect on employee performance at PT. Barito Utama Kantor Cabang Banjarmasin. (2) To find out and analyze whether the leadership style has a partial significant effect on the performance of the employees of PT. MAIN BARITO EARTH. (3) To find out and analyze whether the reward paid partially has a significant effect on the performance of the employees of PT. Barito Utama Kantor Cabang Banjarmasin. This study uses quantitative methods. The population is all employees of PT. Barito Utama Kantor Cabang Banjarmasin.. The sampling technique used is the Saturated Sample / Census, with a sample of 50 respondents. The data analysis technique used is multiple linear regression analysis technique. The results showed that: (1) The leadership style at PT. Bumi Barito Utama does not have a significant effect even though there are Rollingan Leaders or Branch Managers every period (2) the results of the simultaneous calculation include all variables that have a simultaneous effect on changes in the Employee Performance variable (Y) which shows that the percentage contribution of the influence of the dependent variable is 80.7 %. The remaining 19.3% is influenced by variables outside the study. While the results of the partial test with valuet leadership style variable (X1)is -1.814, Reward Punishment (X2) is 8.908. So the Parcial Variable Reward Punishment (X2) has a significant partial effect.